Day 3 Wed, October 30, 2013 2013
DOI: 10.2118/167383-ms
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Integrated Management for New Ventures in High Risk Developing Countries

Abstract: The world is becoming flatter through global integration and ‘smarter’ through interconnected communication and com-merce. For oil and gas organizations this means finding ways to launch business ventures in new regions. While Afghanistan is a high risk zone with negative trade balance, weak currency & infrastructure, extreme security conditions and cultural di-versity, it is estimated to possess substantial reserves of oil and gas that may shake up Central Asia’s increasingly competitive energy contest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…(Estampe, 2014). A number of implementations of various standardized and customized models for performance measurement have been carried out in emerging markets (Allahdad, Bano, & Akhtar, 2012;Asree & Rao, 2011;Banomyong & Supan, 2011;Georgise et al, 2013;Golparvar & Seifbarghy, 2009;Haider, Abdullah, Khalid, Mirajker, & Haider, 2013;McCormack, Ladeira, & de Oliveira, 2008;Reyes & Giachetti, 2010;Salman et al, 2013); out of which SCOR implementations will be discussed in later sections.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(Estampe, 2014). A number of implementations of various standardized and customized models for performance measurement have been carried out in emerging markets (Allahdad, Bano, & Akhtar, 2012;Asree & Rao, 2011;Banomyong & Supan, 2011;Georgise et al, 2013;Golparvar & Seifbarghy, 2009;Haider, Abdullah, Khalid, Mirajker, & Haider, 2013;McCormack, Ladeira, & de Oliveira, 2008;Reyes & Giachetti, 2010;Salman et al, 2013); out of which SCOR implementations will be discussed in later sections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequently, 13 improvement projects were highlighted based on the SCOR best practices and were prioritized. Haider et al (2013) described the implementation of SCOR model in Afghanistan, where suggested actions resulted in considerable improvements like: 9% reduction in import procurement lead-time; and 25% in procurement costs. Bala and Kumar (2011) conducted their study in India and proposed SCOR as the best fitting model for the fast moving consumer goods' (FMCG) supply chains.…”
Section: Scor Applicationsmentioning
confidence: 99%
“…El esquema conocido como Marketing Mix, se encuentra conformado por la mezcla de diversas variables que han ido cambiando según el autor que ha abordado este tema, pero básicamente conserva las clasificadas más comunes, por parte de McCarthy (Haider, Zafar, Khalid, Majid, Abdullah & Sarwar, 2019): Producto, que representa los bienes y servicios que se comercializan en el mercado (Guevara, Álvarez, Villacis, Moreno, Morales & Moreno, 2019).…”
Section: Marketing MIXunclassified
“…Now, if the economy can provide them with employment opportunities and create new jobs for them, Pakistan may make a unique kind of progress. Another change in Pakistan's demographic is that family size is decreasing daily (Belkebir, & Moumen, 2022;Haider et al, 2019). The preferences of parents have changed with the passage of time from large family members to small ones.…”
Section: Introductionmentioning
confidence: 99%